Wavelength selection for spectrally combined laser beams propagating in free space and the atmosphere. (1st March 2023) - Li, Xiaoqing; Yu, Hong; Ding, Zhoulin; Ji, Xiaoling; Friberg, Ari T
Abstract: Wavelength selection has a major impact on spectral beam combining (SBC) of laser beams that propagate in free space and in the atmosphere. We derive analytical expressions for the intensity and four characteristic quality parameters of free-space SBC beams. We show that the peak intensity, the mean-square beam width, and the M 2 factor of an SBC beam at the target are all larger than those of one single laser beam of the same power and average wavelength. The peak intensity can be made higher by increasing the wavelength spacing but reducing the mean wavelength. However, when an SBC laser beam propagates in the atmosphere, the beam quality depends on the absorption coefficient of the multi-wavelength field due to thermal blooming. A thermal distortion number is introduced for an SBC beam and its validity is confirmed. We show that the power proportion of a high-absorption element within an SBC beam should be as low as possible to reduce the thermal blooming effect.